Literasi Digital Untuk Menanggulangi Perilaku Oversharing di Media Sosial - Dewi Bunga; Cokorde Istri Dian Laksmi Dewi; Kadek Ary Purnama Dewi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Social media provides facilities for citizens to exchange information, upload photos, videos and their daily activities. The activity of sharing personal information is too often referred to as oversharing. Psychological oversharing is a human need for attention and social support. But indirectly, this activity actually endangers the uploader. This study will discuss two problems, namely 1) the context of privacy and protection of personal data and its vulnerabilities and 2) digital literacy for the citizen community to overcome oversharing behavior. The concept of privacy basically provides an option for everyone to sort out private and public spaces for themselves. Personal data is transformed into public data when the owner shares the personal data in cyberspace. Digital literacy is needed to protect netizens from threats in cyberspace such as cyberbullying, intimidation, and even direct crimes such as robbery due to the behavior of netizens who show off their wealth on social media. Digital literacy will increase the social intelligence of netizens to determine what can and should be uploaded on social media. Key words: digital literacy, oversharing, social media.